(untitled) (Annals of Medical Research, 2021)
Aim: Anaphylaxis is a severe, potentially life-threatening systemic hypersensitivity reaction. Previous studies reveal that there are many potential deficiencies in the knowledge of doctors regarding the diagnosis and management of anaphylaxis in different health-care settings.The main purpose of this study was to assess the knowledge of 4th-6th-year medical students regarding the diagnosis and management of anaphylaxis.Material and Methods: The study was designed as a cross-sectional survey. The total number of 4th-, 5th-, and 6th-grade medical students at Trakya University Medical School was 651, and 172 (26%) agreed to participate in the study. The participants were asked to answer the questionnaire forms were including the questions assessing students’ knowledge about the diagnosis and management of anaphylaxis, before and after a training session about anaphylaxis.Results:Awareness of students about symptoms indicating anaphylaxis other than cutaneous and respiratory symptoms was between 40% and 77% in the initial test. Although the majority of participants (94%) chose epinephrine as the first-line drug for the treatment of anaphylaxis, correct answers about dosage, concentration, and the route for administration of epinephrine were low when compared with the final test (p 0.001 for each item). While 14% stated they felt they could diagnose and treat anaphylaxis in the initial test, this increased 83% after the training (p 0.001).Conclusion: The study revealed that, knowledge of medical students relating diagnosis and treatment of anaphylaxis is unsatisfactory. Much more attention is needed in medical-school education concerning anaphylaxis management to prevent anaphylaxis-related mortalities in the future.